2010
DOI: 10.1111/j.1440-1630.2010.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Translating knowledge to practice: An occupational therapy perspective

Abstract: Models able to flexibly reflect an occupational therapy perspective of knowledge have a potentially vital role in successful knowledge translation. Furthermore, these models allow therapists and other stakeholders to analyse complex situations and identify targeted knowledge translation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
2
31
0
1
Order By: Relevance
“…Similar to our study, there was evidence of change in the therapist's clinical practice and internal perceptions, in particular confidence, as outcomes of their CPD. Physiotherapists in our study reported practice changes, with particular reference to how they educated patients, and explained the evidence behind their treatment choices, illustrating a knowledge translation process in action [15]. While the journal clubs were the most valued component of the CoP, participants also appreciated the resources that had been created through the CoP, for example, website and shoulder class protocol, which were transferable and sustainable products of the work that had been undertaken, and further spread the knowledge translation process to physiotherapists beyond the CoP.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to our study, there was evidence of change in the therapist's clinical practice and internal perceptions, in particular confidence, as outcomes of their CPD. Physiotherapists in our study reported practice changes, with particular reference to how they educated patients, and explained the evidence behind their treatment choices, illustrating a knowledge translation process in action [15]. While the journal clubs were the most valued component of the CoP, participants also appreciated the resources that had been created through the CoP, for example, website and shoulder class protocol, which were transferable and sustainable products of the work that had been undertaken, and further spread the knowledge translation process to physiotherapists beyond the CoP.…”
Section: Discussionmentioning
confidence: 79%
“…In public health, Higgins, Strange, Scarr, & Pennock et al (2011) explored how practitioners use evidence in practice and found the lack of transferability of statistically based evidence to local communities meant that professional judgements were dependent on a mix of knowledge of the evidence based literature and tacit knowledge based on professional experiences and observations thus building cumulative and shared wisdom. In occupational therapy Metzler & Metz (2010) show how therapists synthesise research based evidence with experiential knowledge when exercising clinical judgement and that the high value placed on research knowledge may result in tacit knowledge being driven underground.…”
Section: Introductionmentioning
confidence: 99%
“…This article introduces the building capacity process, intentionally designed to foster KT within a CoP by involving practitioners in a combination of professional development and community-building strategies (reading, reflection, face-to-face meetings, and online discussions) over an extended period of time to translate knowledge to occupational therapy practice. This research is needed because of the limited KT models developed within occupational therapy (Metzler & Metz, 2010). In this study, we sought to shed new light on KT by addressing the following research questions: (1) Does participation in the building capacity process result in enhanced knowledge of and perceived ability to apply a public health approach to mental health with children and youth and (2) what is the meaning of participation and perceived practice outcomes for occupational therapy practitioners who complete the building capacity process?…”
mentioning
confidence: 99%